A Case of Odontogenic Infection by Streptococcus constellatus Leading to Systemic Infection in a Cogan’s Syndrome Patient - Masanobu Abe; Yoshiyuki Mori; Ryoko Inaki; Yae Ohata; Takahiro Abe; Hideto Saijo; Kazumi Ohkubo; Kazuto Hoshi; Tsuyoshi Takato (Case Reports in Dentistry)
Odontogenic infection in immunocompromised patients tends to extend systemically beyond the oral cavity. Our case report presents a patient with sepsis due to a Streptococcus constellatus (S. constellatus) odontogenic infection in a 64-year-old-immunocompromised woman with Cogan’s syndrome. She had been suffering from chronic mandibular osteomyelitis which was thought to have been caused by dental caries and/or chronic periodontitis with furcation involvement of the left mandibular first molar. We suspect that the acute symptoms of the chronic osteomyelitis due to S. constellatus led to the systemic infection. This infection could be accelerated by the use of a corticosteroid and an alendronate. This is the first report which represents the potential association between odontogenic infection and Cogan’s syndrome.